Integrating Google Sites and project-based learning: Development of digital learning media - Desri Nora; Aldri Frinaldi; Sumanti; Azmi Fitrisia; Hamsidar; Khoirul Amri Rambe (Program Pascasarjana Universitas Negeri Yogyakarta, 2026)
This study aims to develop Google Sites–based learning media integrated with a project-based learning approach for fifth-grade science education and to evaluate its validity, practicality, and effectiveness. The research employed a research and development (R&D) method using the 4D model, consisting of the stages of define, design, develop, and disseminate. The participants were fifth-grade students from three elementary schools: UPT SDN 02 Silaut, UPT SDN 07 Silaut, and UPT SDN 04 Silaut in Pesisir Selatan Regency. Data were collected through validation sheets, practicality questionnaires, and effectiveness tests. The results indicate that the developed media achieved high validity, with material experts rating it at 94%, display experts at 90%, and language experts at 94%, all categorized as “very valid.” Practicality assessments also showed positive responses from teachers (91.73%) and students (89.06%), indicating that the media is “very practical” for classroom use. Furthermore, effectiveness testing demonstrated a significant improvement in student learning outcomes, with the average score increasing from 48.05 in the pre-test to 91.23 in the post-test, resulting in an N-Gain score of 85.47% (high category). These findings suggest that Google Sites–based learning media integrated with project-based learning is a valid, practical, and effective tool for enhancing elementary science learning.